Reducing the risk of post‐endoscopic retrograde cholangiopancreatography pancreatitis using 4‐Fr pancreatic plastic stents placed with common‐type guidewires: Results from a prospective multinational registry. Issue 3 (24th January 2019) - Sahar, Nadav; Ross, Andrew; Lakhtakia, Sundeep; Coté, Gregory A.; Neuhaus, Horst; Bruno, Marco J.; Haluszka, Oleh; Kozarek, Richard; Ramchandani, Mohan; Beyna, Torsten; Poley, Jan W.; Maranki, Jennifer; et al.
Abstract : Background and Aim: Pancreatic plastic stents (PPS) can reduce the risk of post‐endoscopic retrograde cholangiopancreatography pancreatitis (PEP). Prospective multicenter documentation of PEP rate after PPS placement is scarce. A new 4‐Fr stent designed to be deployed over a 0.035‐inch guidewire was used to assess the effectiveness of PEP prophylaxis. Methods: High‐PEP‐risk patients received a 4‐Fr PPS for primary or secondary prophylaxis at seven centers in four countries. Patients were followed until spontaneous PPS migration, endoscopic stent removal, or for 4 months, whichever came first. Main outcome was PEP rate. Results: One hundred six (106) patients received PPS for PEP prophylaxis [61 (58%) primary, 45 (42%) secondary prophylaxis]. Median age was 54 years. Eighty‐one (76%) PPS were placed using a 0.035‐inch guidewire. By investigator choice 99 (93%) stents were single pigtail. Median stent length was 8 cm (range 3–12 cm). Technical success achieved in 100% of cases. Two patients in the primary prophylaxis group (3%, 95% CI 0.4–11%) experienced mild/moderate PEP. Seventy‐eight PPS available for analysis underwent spontaneous migration after a median of 29 days. There were no reports of stent‐induced ductal trauma. Post‐hoc analysis of migration rate by PPS length showed no statistically significant trend. Conclusions: Among high‐risk patients in the primary prophylaxis group, observed rates of PEP are low (3%, 95% CI 0.4–11%) with the use of prophylactic 4‐Fr pancreatic duct stents compatible with a 0.035‐inch guidewire. This low rate is not unequivocally due to the prophylactic stent.